Ranunculales medicinal plants : biodiversity, chemodiversity and pharmacotherapy - Hao, Da Cheng (Academic Press, 2018)
Ranunculales is an order of flowering plants belonging to a paraphyletic group known as the basal eudicots. Medicinal plants of this order provide myriad pharmaceutically active components commonly used worldwide in ethnomedicine and traditional Chinese medicine. Interest in plant-based medicinal resources has led to discoveries of many novel compounds in various species, and to investigations on their chemodiversity, biodiversity and pharmacotherapy. Ranunculales Medicinal Plants covers this order of flowering plants comprehensively in this context; detailing the phytochemistry, chemotaxonomy, molecular biology, and phylogeny of selected medicinal plants families and genera, and their relevance to drug efficacy. The book carries out an exhaustive survey of the literature in order to characterize global trends in the application of flexible technologies. The interrelationship between Chinese species and between Chinese and non-Chinese species is inferred, in the text, through molecular phylogeny, based on nuclear and chloroplast DNA sequencing. The title discusses the conflict between chemotaxonomy and molecular phylogeny, in the context of drug discovery and development. It offers invaluable and holistic coverage for the study of Ranunculales as a pharmaceutical resource.